2019
DOI: 10.3928/01913913-20190909-01
|View full text |Cite
|
Sign up to set email alerts
|

Role of Botulinum Toxin Type A in Cyclic Esotropia: A Long-Term Follow-up

Abstract: Purpose: To describe two patients with childhood cyclic esotropia 8 and 9 years after they underwent botulinum toxin type A treatment to report its long-term outcome. Methods: Two patients with sudden onset cyclic esotropia aged 2 and 4 years were included. Botulinum toxin type A injections were performed on the appropriate muscles. Results: The first patient was a 2-year-old boy with left dominant alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The results with BTXA injection were found to be encouraging in previous reports, including ours. 49 , 50 , 51 In our case study with long-term follow-up of 8 years, we found that BTXA may either provide a cure or break the cycle. 51 Thus, we consider cyclic deviations among the golden indications.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The results with BTXA injection were found to be encouraging in previous reports, including ours. 49 , 50 , 51 In our case study with long-term follow-up of 8 years, we found that BTXA may either provide a cure or break the cycle. 51 Thus, we consider cyclic deviations among the golden indications.…”
Section: Introductionmentioning
confidence: 62%
“… 49 , 50 , 51 In our case study with long-term follow-up of 8 years, we found that BTXA may either provide a cure or break the cycle. 51 Thus, we consider cyclic deviations among the golden indications.…”
Section: Introductionmentioning
confidence: 62%
“…Cyclic esotropia, characterized by periodic cycles of strictly repetitive “straight” and “crossed” eyes, is an extremely uncommon form of nonaccommodative convergent strabismus with an incidence between 1/3000 and 1/5000 and has been reported more commonly than cyclic exotropia or cyclic vertical deviations [ 1 , 2 ]. Most cases occur spontaneously in childhood and are congenital but may be acquired after conditions that disrupt fusion or cause diplopia such as optic atrophy, ocular myositis, trauma, ocular or strabismic surgery, and CNS abnormalities [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonsurgical approaches by botulinum toxin injections to one or both medial rectus muscles may be an alternative way to permanently treat this unique disease. Indeed, an article demonstrated that 2 children with cyclic esotropia were successfully treated with a unilateral or bilateral single dose of botulinum toxin injection for at least 8 years of long-term follow-up [ 2 ]. So, botulinum toxin could be a conservative and predictable alternative way to break the cycle permanently, despite its limitations [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation